2017
DOI: 10.1002/ptr.5885
|View full text |Cite
|
Sign up to set email alerts
|

4,5‐Di‐O‐Caffeoylquinic Acid from Ligularia fischeri Suppresses Inflammatory Responses Through TRPV1 Activation

Abstract: Ligularia fischeri (Ledeb.) Turcz., a perennial plant native to northeastern Asia, has long been used as folk remedies for the alleviation of inflammatory symptoms. We investigated whether the extract of L. fischeri (LFEx) and caffeoylquinic acid (CQA) derivatives, the pharmacologically active ingredients identified from L. fischeri, regulate inflammation via a transient receptor potential vanilloid 1 (TRPV1)-mediated pathway. Changes in intracellular Ca levels to the LFEx and trans-5-O-CQA, 3,4-di-O-CQA, 3,5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Results indicated that the methanol extract of in vitro cultured roots was the richest in 3,5-O-DCQA content, whose concentration was 6 times higher than that in the extract obtained from roots of wild-growing tansy. This is a noticeable result in the manner of industrial production of biologically active 3,5-O-DCQA, which has been shown to have antioxidant, hepatoprotective, antimutagenic, and immunomodulatory activity (Peluso et al 1995;Tatefuji et al 1996;Basnet et al 1996;Yoshimoto et al 2002;Juan-Badaturuge et al 2009;Kim et al 2012Kim et al , 2017. It has also been reported that 3,5-O-DCQA improves pancreatic function in type 2 diabetic mice (Yin et al 2018) and is a potent inhibitor of HIV-1 integrase, an enzyme that is essential for viral replication and subsequent HIV infection of humans (Tamura et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that the methanol extract of in vitro cultured roots was the richest in 3,5-O-DCQA content, whose concentration was 6 times higher than that in the extract obtained from roots of wild-growing tansy. This is a noticeable result in the manner of industrial production of biologically active 3,5-O-DCQA, which has been shown to have antioxidant, hepatoprotective, antimutagenic, and immunomodulatory activity (Peluso et al 1995;Tatefuji et al 1996;Basnet et al 1996;Yoshimoto et al 2002;Juan-Badaturuge et al 2009;Kim et al 2012Kim et al , 2017. It has also been reported that 3,5-O-DCQA improves pancreatic function in type 2 diabetic mice (Yin et al 2018) and is a potent inhibitor of HIV-1 integrase, an enzyme that is essential for viral replication and subsequent HIV infection of humans (Tamura et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…132 Another promising target for the treatment of inflammation is transient receptor potential vanilloid 1 (TRPV1). Kim et al 133 demonstrated that 4,5-DCQA (75) from Ligularia fischeri (Ledeb.) Turcz.…”
Section: Biological Activities Of Natural Cqasmentioning
confidence: 99%
“…esterification of quinide(133) with acid chloride(120) provided a mixture of compounds 134 and 135 (58 and 42%, respectively). The former (134) using H 2 O as a deprotecting agent under reflux led to compound 69 in 27% yield (Scheme 7).…”
mentioning
confidence: 99%
“…LFT is mainly used to treat coughs, ulcers, and tuberculosis as a clinical therapeutic agent [2]. The chemical constituents and pharmacological effects of LFT have been studied previously [3][4][5][6][7]. The plant roots are rich in aroma and volatile oils.…”
Section: Introductionmentioning
confidence: 99%